Gene drives, mosquitoes, and ecosystems: an interdisciplinary approach to emerging ethical concerns - Moreno, Ricardo D.; Valera, Luca; Borgoño, Cristián; Castilla, Juan Carlos; Riveros, José Luis (Frontiers in Environmental Science, 2024)
Gene drives are genetic elements that in sexually reproducing organisms spread faster than those transmitted through a Mendelian fashion. Since gene drives can be engineered to modify different aspects of physiology and reproduction, they have been proposed as a new and revolutionary tool to control vector-borne diseases, particularly those transmitted by the genera Anopheles and Aedes (Culicidae), such as malaria, Dengue and Zika virus. This approach may impact on human health by lowering the transmission of such devastating diseases. However, the release of genetically modified mosquitos (or other species) into the environment raises a series of questions related to the still incipient technology and our present understanding of the complex structure and dynamics of terrestrial and aquatic ecosystems. Moreover, there are ethical concerns about human interventions in natural ecosystems that may eventually impact our way of living or the ecosystems themselves. This work is an interdisciplinary approach that analyzes from a biological, philosophical, and theological perspective the potential ecological impacts on natural environments of the release of genetically modified species, focusing on gene drive-modified mosquitos. It includes theological approach from a Catholic point of view (although it could be easily shared by other Christians) because we hold that world religions give valuable insights even though not everyone may share their groundings. We conclude that the focal problem is the relationship between humans and nature, and the release of genetically modified species may change this relationship unpredictably. However, given the complex interactions in ecosystems, new approaches such as Earth Stewardship principles could provide new and more widely accepted answers involving biological, philosophical, and theological concepts that will help engaging all relevant actors to make a better world.